Why should ecological Marxism be considered in the era of the capitalocene? - Escalera-Briceño, Alejandro (2018)
The objective of this paper is to make inroads into de debates within ecological Marxism in order to underscore the importance of looking at the Marxist categories of historical materialism and dialectics in the light of the ongoing era of the Capitalocene. We began with a summary of recent developments in non-Marxist disciplines that deal with the human / nature interface through hybrid approaches, such as ecological economics and political ecology. With a view of forwarding a proposal for ecological Marxism as a viable and robust alternative, we then mobilize into play several quotations from Marx on the subject, in order to lead us into the current debates between, mainly, Bellamy Foster and Jason Moore. We suggest that in the Capitalocene, purveyor great threats to the planet, humanity and capitalism itself, those debates can offer very worthwhile readings of the contradictions of advanced capitalism.